Pendampingan Penguatan Pemahaman Fiqh Munakahah Pada Remaja Pra Nikah Di Dusun Jati Krenceng Kab. Kediri - Muhammad Idrus; ahmad fauzi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Marriage is one of the shari'ah in Islam and is a shari'a that will remain valid in heaven later. Everyone must expect a marriage and live a harmonious family life sakinah mawaddah and warohmah. However, there are many cases of families running aground in the middle of the road caused by various ospek, be it from communication between the two partners, negligence of the obligations of husband or wife and so on. Fiqh munakahah is a science that discusses marriage be it understanding, laws, obligations of husband and wife and so on. So for Muslim families in order to build a harmonious family, happy afterlife world then must learn fiqh munakahah. In order to understand and know whether their marriage is legal, it is still a married couple or their marriage is still legal. Therefore it is mandatory for every prospective husband and wife to learn fiqh munakahah first before carrying out the wedding.